Case report: Sequential therapy with dupilumab and baricitinib for severe alopecia areata with atopic dermatitis in children - Fang, Huijuan; Zhang, Fengchuan; Lin, Wenjun; Jiang, Yuqi; Liu, Qingwu; Yang, Dingquan (Frontiers in Immunology, 2024)
An 8-year-old female child presented with patchy hair loss for 1 year, accompanied by eyebrow loss for 6 months. Microscopic examination of the hair confirmed the features of active stage alopecia areata, with a Severity of Alopecia Tool (SALT) score of 70%. The diagnosis was severe alopecia areata. The patient had a history of atopic dermatitis since infancy, with recurrent episodes of scattered papules and pruritus for 8 years. Initial treatment involved subcutaneous injections of dupilumab 300mg every 2 weeks for 6 months, resulting in a reduction of SALT score to 20% and improvement of atopic dermatitis symptoms. Discontinuation of Dupilumab and initiation of daily oral Baricitinib at a dose of 2mg for a duration of 5 months. According to the SALT score evaluation, the severity of hair loss was less than 10% and there was significant regrowth of hair. No significant adverse reactions were observed during the treatment period.